Effects of Salinity on the Growth, Physiological Characteristics, and Intestinal Microbiota of the Echiura Worm (Urechis unicinctus) - Qiaojun Zheng; Yunjian Wang; Jiao Chen; Yunpeng Li; Feng Zhao; Danwen Liu; Maokai Wei; Dexu Kong; Zongtao Chen; Zhifeng Zhang; Yubin Ma (Frontiers in Marine Science, 2022)
Intertidal biota is subjected to significant fluctuations in salinity. Urechis unicinctus , a typical species thriving in intertidal sediments, have relatively simple anatomy structure and therefore could be considered as an ideal species for salinity acclimation. Moreover, due to the high nutrients, U. unicinctus has become an emerging aquaculture species in China. In this study, we investigated the effects of salinity on the growth performance, coelomic fluid biochemical indices, antioxidant enzyme system, Na + /K + -ATPase, and non-specific immune enzyme activities, as well as intestinal microbiota composition of this species in an 8-week experiment. The results indicated U. unicinctus is a euryhaline species that can tolerate salinities from 15‰ to 40‰ and demonstrated the highest growth performance at 30‰. Physiological characteristic analyses of coelomic fluid and intestines indicated that the salinity range of 15‰ to 30‰ is more suitable, while 10‰ and 40‰ salinity ranges seem unsuitable for juvenile U. unicinctus . Furthermore, intestinal microbiota analysis indicated salinity had a significant effect on the composition structure. KEGG pathway analysis indicated that antioxidant related metabolic pathways and amino acid metabolic pathways may play important roles in gut microbiota under salinity stress. Comprehensive analysis of intestinal bacteria and enzyme activities indicated Unidentified Rhodobacteraceae, Vibrio , and Shimia may play important roles in high salinity acclimation, while Legionellaceae may act as important microbiota in low salinity acclimation. Moreover, Ruminococcus , Oscillospira , Lachnospiraceae, Clostridiales, and S24-7 showed negative correlations with the antioxidant and nonspecific immune enzymes, indicating that these bacteria can be considered as important candidates of probiotics for U. unicinctus aquaculture industry. The findings of this study will extend our understanding of the effects of salinity on the growth and health of U. unicinctus and contribute to a better understanding of the salinity acclimation strategies of organisms in intertidal zones.